2021
DOI: 10.3390/foods10102492
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Probiotic Lactiplantibacillus plantarum 299v in the Technology of Non-Dairy Ice Cream Based on Avocado

Abstract: Food enriched with probiotics and prebiotics belong to the class of novel foods. Functional food, apart from its nutritional function, has an additional pro-health effect. The aim of the presented study was to create a concept of a functional dessert—avocado-based non-diary ice cream enriched with probiotic bacteria Lactiplantibacillus plantarum 299v. The product was tested for the survival of bacteria in various conditions, and the influence of the probiotic on the physicochemical and organoleptic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This means better support for the probiotic cells in the ice cream matrix due to the high proportion of probiotics. This assumption is supported by Krawęcka et al (2021) who reported that adding bananas to ice cream helps maintain the viability of probiotics during freezing due to their polysaccharide content.…”
Section: Synbioticmentioning
confidence: 73%
“…This means better support for the probiotic cells in the ice cream matrix due to the high proportion of probiotics. This assumption is supported by Krawęcka et al (2021) who reported that adding bananas to ice cream helps maintain the viability of probiotics during freezing due to their polysaccharide content.…”
Section: Synbioticmentioning
confidence: 73%
“…The cultivar, origin and ripeness degree of fruits are the factors that most influence the fruit quality and derivative products, such as sorbets [46,47]. Some studies also indicate that functional frozen probiotic desserts may be obtained by supplementation with probiotic bacterial strains, using riceberry and sesame milk as a base, instead of vegetables and fruits [18,[48][49][50].…”
Section: The Lactic Acid Fermentation Process and Choice Of Food Matrixmentioning
confidence: 99%
“…However, because of the freezing, freezing storage and air incorporation processes, the frozen dessert manufacturing process may reduce the probiotic survival in the goods [48]. Prebiotic substances may shield the beneficial cultures during production, storage and simulated gastrointestinal conditions.…”
Section: Selection Of Bacterial Strains With Probiotic Propertiesmentioning
confidence: 99%
“…Functional food is a kind of food with special physiological effects to improve health status or reduce illness (2023). Among these, foods containing or fermented with probiotics have been proved to be safe and edible (Krawecka et al., 2021), which enhance host metabolism by generating new cells and altering the structure of the intestinal microflora (Rabah et al., 2017). Therefore, it is very important for the functional food industry to develop foods containing probiotics.…”
Section: Introductionmentioning
confidence: 99%